'A statement against the totalitarian countries of Europe': human rights and the early Cold War. Issue 2 (2nd April 2016) - Baudet, Floribert
Abstract: This article discusses scholarly views on the rise of the human rights paradigm. Based on a case study of the Netherlands it argues that the appeal of human rights cannot simply be attributed to the memory of the Holocaust, or the rise of post-war generations disillusioned with traditional ideologies in the 1960s and especially, the 1970s. Instead, it proposes that human rights primarily owe their popularity to the ideological contest of the Early Cold War, even though means to convey the message all over the world were only available in the decades that followed.